Comparative evaluation of the antiplaque effectiveness of green tea catechin mouthwash with chlorhexidine gluconate - Harjit Kaur; Sanjeev Jain; Amritpal Kaur (Wolters Kluwer Medknow Publications, 2014)
An increasing number of people all around the world are turning to the nature by using the natural herbal products. Green tea with active chemical ingredients possesses diverse pharmacological properties. Aim: The aim of this study is to compare the antiplaque efficacy of green tea catechin mouthwash with chlorhexidine gluconate mouthwash. Materials and Methods: A single blinded cross-over study was conducted among 30 participants in the age group of 18-25 years. The mouthwash samples for the study were previously labeled assigning the letters: A (0.25% of green tea catechin mouthwash) and B (0.12% of chlorhexidine mouthwash). The study subjects were randomly divided into two groups of 15 each and the study was divided into two phases. In phase I, the mouthwash A was given to one group and other group was given mouthwash B. After a 15 day washout period, in phase II, both groups were given other mouthwash. At the end of each phase of 1 week, plaque score was recorded by using Turesky modification of the Quigley-Hein plaque index. Results: The plaque scores were compared and the difference between the green tea catechin and chlorhexidine mouthwash was determined by t-test. The difference between plaque scores were not statistically significant (P > 0.05). The results showed that both the groups that is green tea catechin mouthwash (0.25%) and chlorhexidine mouthwash (0.12%) have comparable results in plaque reduction. Conclusion: This study supports the effectiveness of green tea catechin mouthwash as an antiplaque agent. It should be explored as a cost-effective, long-term antiplaque rinse with prophylactic benefits.